Tiga Mental Pemenang (Kajian Tematik Ayat 200 Surah Ali Imron) - Muhith Muhith (STID DI AL-HIKMAH, 2016)
Mental readiness determine the success of any competition, including in the propaganda. With good mental person will not experience despair when a failure and will not forget yourself when success. Events of the battle of Badr and Uhud provide important lessons for preaching trip along history. Surah Ali Imran summarizes the events and provide important notes on the last paragraph that could be understood as conclusion well as recommendations for the preachers in upholding truth wherever and whenever they are. Shabar, ribath and piety, are three properties that are called to the believers to achieve success